2021
DOI: 10.3390/ijms22084179
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Effect of Downregulation of the Opioid System in Mouse Model of Different Activity of the Endogenous Opioid System

Abstract: The opioid system is well-known for its role in modulating nociception and addiction development. However, there are premises that the endogenous opioid system may also affect blood pressure. The main goal of the present study was to determine the impact of different endogenous opioid system activity and its pharmacological blockade on blood pressure. Moreover, we examined the vascular function in hyper- and hypoactive states of the opioid system and its pharmacological modification. In our study, we used two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…72 Furthermore, naloxone administration attenuated the development of hypertension in the spontaneously hypertensive rat model known to show sympathetic and RAS activation. 20,28,29 In the current study, the Ang II-induced ex vivo constriction was increased in IUME rats while the expression of AT1R and ACE were downregulated in the aorta, heart, and kidney (data not shown). This finding suggests the increased Ang IIinduced constriction is most likely facilitated by the ORs, potentially increasing the affinity to AT1R and amplifying the signaling cascade, as we showed that blocking ORs with naloxone can revert this effectherefore, IUME could induce chronic activation of the AT1R potentially enhanced by the heterodimerization with µ-OR, resulting in reduced AT1R expression.…”
Section: Original Articlementioning
confidence: 51%
See 3 more Smart Citations
“…72 Furthermore, naloxone administration attenuated the development of hypertension in the spontaneously hypertensive rat model known to show sympathetic and RAS activation. 20,28,29 In the current study, the Ang II-induced ex vivo constriction was increased in IUME rats while the expression of AT1R and ACE were downregulated in the aorta, heart, and kidney (data not shown). This finding suggests the increased Ang IIinduced constriction is most likely facilitated by the ORs, potentially increasing the affinity to AT1R and amplifying the signaling cascade, as we showed that blocking ORs with naloxone can revert this effectherefore, IUME could induce chronic activation of the AT1R potentially enhanced by the heterodimerization with µ-OR, resulting in reduced AT1R expression.…”
Section: Original Articlementioning
confidence: 51%
“…Preclinical reports have shown opiates as important modulators of cardiovascular function in both normotensive and hypertensive states, and studies have reported that EOPs are elevated in models of hypertension of various causes, including genetic and renovascular hypertension. 29,74 The levels of EOPs fluctuate during the lifespan. Physiologically, β-endorphin plasma levels increase during pregnancy from week 6 (20 fmol/mL) to delivery (>120 fmol/mL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we found that HA mice had an increased BP when exposed to NAL for one week. Interestingly, mice with low swim stress-induced analgesia (LA) had a higher basal BP level than HA mice, but NAL treatment had no effect on BP [ 13 ]. Therefore, in this study, we aimed to further investigate this effect using selective opioid receptor antagonists to evaluate which opioid receptors (μ, δ, or κ) influence the BP level.…”
Section: Introductionmentioning
confidence: 99%